Marketing strategies for creating national wealth for strategic implementation - Tripunoski, Mirko; Nikolovski, Aleksandar; Matovska, Mirjana (REGIONAL AND BUSINESS STUDIES, 2011)
The main factors in creating national wealth and in their strategic implementation are a productive and efficient economy, a good social system, and a good aiding process. Every country (state) develops its own strategies for creating national wealth to achieve the following goals: Designing an effective national strategy, Defining a strategic base, Designing a strategic position, and Designing a strategic implementation. We will elaborate the formation of a strategic base through the creation of social needs within the evaluation of the existing compatible inner and outer environment of the nation. Through them we are going to set the national goals and tasks regarding the environment, by analyzing the: Global economic structure, influence of global forces and trends, and Analysis of national concepts. We will elaborate the strategic position and its design through national growth strategies, concentrated in pragmatic and concrete guidelines for the identification of specific public policies regarding the improvement of competitiveness as basic and primary state politics and state supporting policies. The designing of the national strategic implementation will be classified through the following thematic elaboration: The state as an initiator of wealth, The state as a protector of wealth, The state as the regulator of wealth, The state as the mediator of wealth. The paper elaborates several elements that are crucial for the implementation of the national strategies for creating wealth through: Evaluation of the advantages and weaknesses of the state, Dilemmas, the balance between different political options, Creating a healthy relation between the country and the business, Increasing the cooperation between the different governments of the region.Keywords: strategies, national wealth, implementation, values, concepts, beliefs, culture, economy, basic position, basic global economic structure, regional mediator, protective, initiator